Patterns of injury and pathology in paediatric deaths processed at the Johannesburg Forensic Pathology Service over the period 2009 - 2011 - Thornton, Roxanne (My University, 2015)
Within the field of paediatric pathology dominant universal trends have emerged with child abuse related fatalities and child murders being at the forefront. However, several authors have noted that such trends have not been documented within the South African context. This is due to the lack of data collection and research within South Africa. Patterns of injury and prevalence of paediatric fatalities received at the Johannesburg Forensic Pathology Service (JHB FPS) over three years were observed through a descriptive, retrospective study. Data were collected from FPS case files and Police reports (SAPS180) accompanying the body to the mortuary. The results indicated that the majority of paediatric deaths were due to blunt force injuries, natural disease processes and drowning. Subdural and subarachnoid haematomas, multiple blunt force internal injuries, hyperinflation and consolidation of the lungs and features of dehydration were the dominant patterns of injuries and disease. Additionally, results exhibited a significant difference in age range when correlated to category of death as well as a high risk of mortality within the first year of life. This study highlights the alarming figures of accidental and socio-economic paediatric death cases which are received at the JHB FPS. Keywords: Child mortality, Injury patterns, Forensic Pathology
Division of Forensic Medicine and Pathology, University of the Witwatersrand Submitted in fulfilment of the requirements for the degree of Masters of Science in Medicine In the Health Science Faculty University of Witwatersrand Johannesburg 2014
Keywords: child mortality; injury patterns; forensic pathology; Forensic Medicine--in infancy & childhood; Infant Mortality--South Africa